Relationship Between Initial Vancomycin Trough Levels and Early-Onset Vancomycin-Associated Nephrotoxicity in Critically Ill Patients. Issue 1 (February 2018) - Chuma, Masayuki; Makishima, Makoto; Imai, Toru; Tochikura, Naohiro; Suzuki, Shinichiro; Kuwana, Tsukasa; Sawada, Nami; Komatsu, Tomohide; Sakaue, Takako; Kikuchi, Norikazu; Yoshida, Yoshikazu; Kinoshita, Kosaku
Abstract : Background: Appropriate initial dosing of vancomycin (VCM) is important in improving survival and in preventing nephrotoxicity in critically ill patients, but the potential relationship between initial VCM trough levels and early-onset nephrotoxicity remains unclear. We examined the relationship between initial VCM trough levels and early-onset VCM-associated nephrotoxicity. Methods: We performed a retrospective study of patients who had therapeutic drug monitoring of VCM with initial trough levels within 4 days after the beginning of VCM administration. We excluded patients who received renal replacement therapy from 2 days before to 7 days after the beginning of VCM administration, were younger than 18 years, or had renal dysfunction before the beginning of VCM administration. Early-onset VCM-associated nephrotoxicity was defined as an increase in serum creatinine level of ≥0.5 mg/dL (44.2 μmol/L) or 50% above baseline for 2 or more consecutive days within 7 days after the beginning of VCM administration. Results: Among 109 enrolled patients, 13 patients had early-onset VCM-associated nephrotoxicity. Its incidence rate was 31.3% in patients with initial trough levels of ≥20g/mL, which was significantly higher than 6.3% in patients with initial trough levels of <10 mg/L. Multiple logistic regression analysis demonstrated that early-onset VCM-associated nephrotoxicity was associated with initial trough levels of ≥20 mg/L (odds ratio, 5.0; 95% confidence interval, 1.3–19.1) and with vasopressor use (odds ratio, 5.0; 95% confidence interval, 1.3–19.1). Kaplan–Meier analysis showed that the probability of nonnephrotoxicity for patients with initial VCM trough levels of ≥20 mg/L was lower compared with patients with trough levels of <15 mg/L. Conclusions: Initial trough levels of ≥20 mg/L but not ≥15 mg/L were associated with early-onset VCM-associated nephrotoxicity in critically ill patients. Future prospective studies are needed to examine outcomes in critically ill patients achieving initial VCM trough levels of 15–20 mg/L.